VAYU PURIFIER - RAVIKIRAN, K.; ARCHANA, B.; SATHISH, K.; RAHUL, M.; ANIRUDH, D. (The journal of contemporary issues in business and government, 2022)
Air pollution is a major health hazard affecting the developing and developed countries alike. The effect of air pollution on health is complex and their individual impact varies from one to another. It is not only the ambient air quality in the cities but also the indoor air quality in the rural and urban area that are causing concern. In fact, in the developing world the highest air pollution explosion occurs in indoor environment. The main objective of our project is to reduce the air pollution. We live in a world where everything is transported by the use of vehicles, so it is necessary to have knowledge about vehicle pollution. But before that let us talk about pollution. Pollution is the introduction of harmful materials into the environment. These harmful materials are called pollutants. Similarly, vehicle pollution is the introduction of harmful pollutants into the environment by motor vehicles.To overcome this, we present a solution which prevents pollutants in the air.